2021
DOI: 10.1101/2021.10.28.466251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACTN2mutant causes proteopathy in human iPSC-derived cardiomyocytes

Abstract: RationaleGenetic variants in ACTN2, encoding α-actinin 2 (ACTN2), are associated with several forms of (cardio)myopathy in the heterozygous state, and can cause progressive, severe cardiomyopathy in the homozygous state. We previously reported a heterozygous missense (c.740C>T) ACTN2 variant, associated with hypertrophic cardiomyopathy (HCM), which induced an electro-mechanical phenotype in human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs).ObjectiveTo evaluate the impact of heterozygosi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…A study of an HCM-associated variant, T247M, established in iPSC-derived cardiomyocytes, showed that the variant is disruptive at the cellular level, inducing HCM phenotypes, including Z-disk myofibrillar disarray and disrupted contractility [16]. Moreover, T247M, like A119T, caused α-actinin-2 aggregation and reduced incorporation into Z-disks [29]. How the T247M variant impacts actin binding is not known.…”
Section: Introductionmentioning
confidence: 99%
“…A study of an HCM-associated variant, T247M, established in iPSC-derived cardiomyocytes, showed that the variant is disruptive at the cellular level, inducing HCM phenotypes, including Z-disk myofibrillar disarray and disrupted contractility [16]. Moreover, T247M, like A119T, caused α-actinin-2 aggregation and reduced incorporation into Z-disks [29]. How the T247M variant impacts actin binding is not known.…”
Section: Introductionmentioning
confidence: 99%